Complex fuzzy soft group - Alsarahead, Mikhled O.; Abd Ghafur Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2017)
In this paper, we define complex fuzzy soft group and introduce some new concepts such as complex fuzzy soft functions and homogeneous complex fuzzy soft sets. Then we investigate some characteristics of complex fuzzy soft group.The relationship between complex fuzzy soft group and fuzzy soft group is also investigated. It is found that every complex fuzzy soft group yields two fuzzy soft groups. Finally we define the image and inverse image of a complex fuzzy soft group under complex fuzzy soft homomorphism and we study their elementary properties.